Case Study on the design optimization of the positive pressure operating room - Ghaim Man Oo; Komsilp Kotmool; Mongkol Mongkolwongrojn (Scientific Reports, 2024)
and BCP concentrations. The investigated operating room could host up to ten surgical members with the optimum overpressure of 5.89 Pa and 0.56 m/s of supply velocity under the standard cleanliness level. Modifying the supply surface area will enhance the performance of the operating room by providing a cleaner zone and maintaining the desired room pressure, even with a low airflow rate. This optimization scheme could guide practical applications in all positively pressurized operating rooms to address issues related to overpressure effects.
Keywords: Surgical Simulation and Training; Radiative Heat Transfer Studies; Thermoregulation and physiological responses